Parallel trials in Spain: The adverse effect of freedom of information on the principle of publicity - Cristina San Miguel Caso (Revista Brasileira de Direito Processual Penal)
The informative methodology of the media has undergone a remarkable evolution caused by the impact of new technologies in the communication sector. This has led to an intensification of the coverage of information on judicial issues generating the media phenomenon of the so-called parallel trials. Thereby, we face an extrajudicial nature phenomenon that is significant enough to produce serious interference in a criminal process. The objective of this work is to analyze the incidence of parallel trials in relation to the principle of publicity from the procedural perspective, examining, subsequently, the role played by the communication offices of the Judiciary of Spain in the transmission and dissemination of judicial information as one of the possible solutions to mitigate, eventually, the pernicious effects of parallel trials in the process. To this end, we intend to answer several questions: Is media justice the adverse effect of the inadequate exercise of informational freedoms? Has a reversal in the principle of publicity for the investigated subject been produced? Are communication offices a solution to parallel trials?